Fish Growth Performance in RAS Pond Using Hydrocyclone Mechanical Filter - Aulia Rahmawati; Febriyani Eka Supriatin; Sri Andayani; Muhammad Nasim Mubarok; Aulia Rahman (Jurnal Penelitian Pendidikan IPA, 2024)
The high feeding and the metabolic output of the fish in intensive aquaculture can cause various problem, such as poor water quality and slowing down the fish growth performance. Recirculating Aquaculture System (RAS) is a solution to maintain water quality. Unfortunately, the conventional mechanical filter in RAS such as japmat is inefficient. One strategy that can be applied is to use a hydrocyclone. This research aims to observe the fish growth performance in RAS pond using hydrocyclone mechanical filter and its comparison with the use of japmat. Research method was performed by comparing hydrocyclone and japmat in the pond with the RAS system. The research design is completely randomized design (CRD), with three replications in each treatment. The research was carried out through five stages, namely hydrocyclone set-up, RAS ponds set-up, water quality analysis, fish growth measurement, and statistical analysis. Based on the Independent Samples Test, the use of hydrocyclone mechanical filters has a significant effect (P<0.05) on the measured water quality parameters (DO, Temperature, pH, TDS, NH3) except for NO2. Hydrocyclone significantly affect Average Daily Growth and Specific Daily Growth parameters. Whilst, the Survival Rate and Feed Conversion Ratio parameters, it did not give significant effect